2021
DOI: 10.1126/scitranslmed.abg8693
|View full text |Cite
|
Sign up to set email alerts
|

Dual targeting of CTLA-4 and CD47 on T reg cells promotes immunity against solid tumors

Abstract: Blockade of CD47, the “do not eat me” signal, has limited effects in solid tumors despite its potent antitumor effects in hematopoietic malignancies. Taking advantage of the high expression of cytotoxic T lymphocyte–associated protein 4 (CTLA-4) on Treg cells and abundant Fc receptor–expressing active phagocytes inside the tumor microenvironment (TME), we designed and tested a heterodimer combining an anti–CTLA-4 antibody, which targets Treg cells, with the CD47 ligand, signal regulatory protein α (SIRPα), to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 54 publications
1
38
0
Order By: Relevance
“…Of note, previous studies have identified combination inhibition of CD47 and PD-L1 could lead to a synergistic inhibition effect on tumor growth in some pancreatic cancer cell lines 38 . Combination blockade of CD47 and PD1, CTLA4 also achieved better anti-tumor effect 34 , 37 . Furthermore, a couple of ongoing clinical trials are targeting dual immune checkpoints such as CD47/PD-1(HX009), CD47/CD137 (DSP107), CD47/PD-L1 (IBI322, PF-07257876), CD47/CD20 (IMM0306), CD47/CD19 (TG-1801) 49 .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Of note, previous studies have identified combination inhibition of CD47 and PD-L1 could lead to a synergistic inhibition effect on tumor growth in some pancreatic cancer cell lines 38 . Combination blockade of CD47 and PD1, CTLA4 also achieved better anti-tumor effect 34 , 37 . Furthermore, a couple of ongoing clinical trials are targeting dual immune checkpoints such as CD47/PD-1(HX009), CD47/CD137 (DSP107), CD47/PD-L1 (IBI322, PF-07257876), CD47/CD20 (IMM0306), CD47/CD19 (TG-1801) 49 .…”
Section: Discussionmentioning
confidence: 97%
“…Targeting CD47 in combination with PD-1 may potentially improve the outcomes of patients with anaplastic thyroid carcinoma 36 . Similarly, Dual targeting CD47 and CTLA-4 promotes immunity against colon cancers 37 . Anti-CD47 targeting in pancreatic cancer could remodel tumor- infiltrating immune cells 38 and enhance CD19/CD3-bispecific T cell engager antibody-mediated lysis of B cell malignancies 39 .…”
Section: Introductionmentioning
confidence: 99%
“…IL-2 was fused with Fc with a GGGGS linker and cloned into pEE6.4. Heterodimerization of Ab–IL-2 was achieved by the knobs-into-holes approach ( 52 ). Plasmids encoding Ab-Fc and IL-2–Fc were cotransfected into FreeStyle 293-F cells (Thermo Fisher Scientific).…”
Section: Methodsmentioning
confidence: 99%
“…Based on the high expression of cytotoxic T lymphocyte-associated protein 4 (CTLA-4) on regulatory T (Treg) cells and abundant Fc receptor-expressing active phagocytes inside the TME, preclinical study had been done by combining anti-CTLA-4 mAbs with the SIRPα, targeting Treg cells and selectively blocking CD47 on intratumoral Treg cells, respectively. The results demonstrated that simultaneously modulating both "eat me" and “do not eat me” signals induced Treg cell depletion inside the TME and could be an effective strategy for treating solid tumors [ 81 ].…”
Section: Cd47 Combination Therapiesmentioning
confidence: 99%